Quantifying impacts of two ENSO patterns on South China sea summer monsoon onset - Lianyi Zhang; Junshu Lin; Zesheng Chen; Yanping Shi; Yan Du (Geoscience Letters)
Abstract The onset of the South China Sea (SCS) Summer Monsoon (SCSSM) is usually in May, strongly influencing the beginning of the wet season over the surrounding regions, such as South China and the Philippine Islands. The onset date is significantly affected by the El Niño-Southern Oscillation (ENSO), which manifests as two major types: the Eastern-Pacific (EP) and Central-Pacific (CP) patterns. However, the impacts of these patterns on the SCSSM onset await quantification. Here, using a novel statistical metric, binary combined linear regression, we find a dominant role of the CP pattern rather than the EP pattern, as a moderate CP El Niño/La Niña tends to cause SCSSM onset delay/advance by around 4.7/5.1 days in its decaying year. The anomalous SST structure of CP El Niño leads to persistent anomalous anti-cyclonic winds over the western North Pacific from April to June, suppressing the local convection and impeding the SCSSM winds. In comparison, the EP El Niño impact decays quickly in May and hardly affects the SCSSM onset. This, hence, weakens the relationship between the SCSSM onset and ENSO. These results help improve the SCSSM onset prediction by involving diverse ENSO impacts.